Introduction: Studying policy styles at the national level and beyond - Howlett, Michael; Tosun, Jale (The Routledge handbook of policy styles, 2021)
The essence of a policy style resides in how governments around the world enact their policies, including how they articulate policy options or solutions to address complex policy problems such as environmental degradation or social inequality. Not all policies are formulated or implemented in the same way and governments differ in terms of how they make decisions and how they interact with their civil services and the public in so doing. This handbook consolidates the state of knowledge on policy styles, an older emphasis in public policy studies that has re-emerged in the last decade. It follows up on studies of national-level styles found in the 2019 Routledge volume Policy Styles and Policy-Making edited by Michael Howlett and Jale Tosun, but expands that study to many others levels of analysis and instances of government decision-making in which discernible styles develop and persist in affecting policy-making. Uniting theoretical bases and advancements in practice, the essays in this handbook constitute a pioneering effort combining the efforts of many leading experts into a single comprehensive overview of the subject. This chapter spells out these aims and the scope of the chapters it contains.